Dynamics of quantum entanglement in a zigzag graphene nanoribbon. (1st July 2021) - Tan, Xiao-Dong; Cui, Le; Song, Ya-Feng
Abstract: We study the dynamics of entanglement between two edge spins in a zigzag graphene nanoribbon (ZGNR) which is thermalized with a reservoir at temperature T . The results show that the entanglement evolution displays oscillating behaviors in the presence of an external magnetic field. Such oscillating behaviors of entanglement strongly depend on the field frequency and relative location between two inter-edge coupled spins. At some critical field frequencies, the entanglement exhibits a periodic structure. When the temperature is low, the oscillating patterns of entanglement are quite regular and symmetrical. When the temperature is high, the patterns of entanglement evolution occur irregular distortions due to the thermal fluctuations. However, the entanglement between two inter-edge coupled spins in ZGNR still exists a nontrivial value even at room temperature.